THU0093 Deiminated Histone 4 from Neutrophil Extracellular Traps is a Novel Autontigen in Rheumatoid Arthritis. (23rd January 2014) - Migliorini, P.; Pratesi, F.; Dioni, I.; Alcaro, M. C.; Paolini, I.; Panza, F.; Rovero, P.
Abstract : Background: Histone deimination is a crucial event in cell biology, regulating gene function and contributing to antimicrobial response, through the formation of neutrophil extracellular traps (NETs.) Deiminated proteins are target of ACPA in rheumatoid arthritis. Objectives: Aim of the present study is to to investigate the presence in RA sera of a new subset of ACPA, antibodies reactive with deiminated histones. Methods: Neutrophils from peripheral blood were stimulated with calcium ionophore; NETosis was induced by phorbol myristate acetate and NET proteins were isolated. Sera were tested by immunoblot on acid extracted proteins from neutrophils and from NETs and by ELISA on deiminated histone H4 or H4-derived peptides. Bands reactive with RA sera were digested with trypsin and subjected to MALDI-TOF analysis, before and after derivatization to detect citrullinated peptides. Results: RA sera reacted with an antigen of 11 KDa expressed in nuclei of activated neutrophils, identified as H4. MALDI TOF analysis indicated that this antigen, present also in NETs, is citrullinated. By ELISA, RA sera bound in vitro citrullinated H4. Citrullinated H4 14-34 and 31-50 peptides detected antibodies in 67% and 63% of RA sera and in less than 5% of controls; antibody titer was correlated with anti-CCP2. Conclusions: Citrullinated H4 from activated neutrophils and NETs is a target of antibodies in RA and synthetic citrullinated H4-derived peptides are a new substrate for ACPA detection. As NETosis can generate antigens for ACPA, these data suggest a novel connection between innate and adaptive immunity in RA. Disclosure of Interest: None Declared